Goal-Free Evaluation Approach in Providing Feedback on The Motivation and Learning Outcomes of P of Grade IV Students - Ketut Dian Setiawidiantari; Gede Wira Bayu; I Wayan Ardana (Universitas Pendidikan Ganesha, 2025)
Student motivation and learning outcomes are often influenced by the learning methods and feedback provided by the teacher. Conventional approaches tend to focus on achieving the final goal, thus ignoring the overall student learning process. This study aims to describe the effect of the Goal Free Evaluation (GFE) approach in providing feedback on the learning motivation and PPKn learning outcomes of fourth grade elementary school students. This study used a quasi-experimental design with a nonequivalent control group pretest-posttest design. The subjects of the study were fourth grade elementary school students who were divided into two groups, namely the experimental class using the GFE approach and the control class using the conventional method. Data were collected through learning outcome tests and motivation questionnaires. Data analysis was carried out by comparing the average scores between the two groups. The results showed that the average motivation score in the experimental class was higher (17.83) than the control class (15.14), and the learning outcomes of students in the experimental class were also higher (82.67) than the control class (81.21). The conclusion of this study shows that the GFE approach has a positive effect on increasing student motivation and learning outcomes. The implication is that this approach can be applied as an alternative to improve the quality of learning and evaluation in schools.